The Impact of Potassium Binders on Mortality in Patients with Hyperkalemia: A Single-Center Study - Hajime Nagasu; Atsuyuki Tokuyama; Eiichiro Kanda; Seiji Itano; Seiji Kishi; Tamaki Sasaki; Naoki Kashihara (MDPI AG, 2023)
Hyperkalemia is associated with an increased risk of mortality and is a common complication in patients with chronic kidney disease (CKD). Despite the prevalence of hyperkalemia, current real-world data suggest that serum potassium levels are not effectively managed in clinical practice. The potential benefit of potassium binders in reducing the risk of death has not been thoroughly investigated. Therefore, this retrospective cohort study aimed to investigate the potential impact of potassium binders on mortality risk in patients with CKD by analyzing electronic medical records. The study included 1689 patients with CKD and hyperkalemia (serum potassium level > 5.0 mEq/L), who visited Kawasaki Medical School Hospital between January 2014 and December 2018. The patients were divided into two groups: those without CPS (calcium polystyrene sulphonate) treatment (CPS_OFF) and those with CPS treatment (CPS_ON). The results showed that the incidence of death was significantly higher in the CPS_OFF group than in the CPS_ON group (22.3% vs. 19.6%, p < 0.001). After propensity score matching, the CPS_ON group had a higher survival rate than the CPS_OFF group (log-rank test, p = 0.020). These results suggest that potassium binders may reduce the risk of death in patients with CKD and hyperkalemia. We hope that the results of this cohort study will be confirmed in future RCTs.